1999
DOI: 10.1093/emboj/18.13.3712
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome structure completely inhibits in vitro cleavage by the V(D)J recombinase

Abstract: Lineage specificity and temporal ordering of immunoglobulin (Ig) and T-cell receptor (TCR) gene rearrangement are reflected in the accessibility of recombination signal sequences (RSSs) within chromatin to in vitro cleavage by the V(D)J recombinase. In this report, we investigated the basis of this regulation by testing the ability of purified RAG1 and RAG2 proteins to initiate cleavage on positioned nucleosomes containing RSS substrates. We found that nicking and double-strand DNA cleavage of RSSs positioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 60 publications
4
94
0
Order By: Relevance
“…Recent data suggests that nucleosomal remodeling may be the critical change required to allow the V(D)J recombinase access to target sites (15,38,39). The role of demethylation may be to alter the chromatin structure of the kappa locus, providing a permanent change in the accessibility of the locus for transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggests that nucleosomal remodeling may be the critical change required to allow the V(D)J recombinase access to target sites (15,38,39). The role of demethylation may be to alter the chromatin structure of the kappa locus, providing a permanent change in the accessibility of the locus for transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have confirmed that nucleosome position can influence V(D)J cleavage (20,21). An RSS assembled into a mononucleosome is refractory to cleavage by the Rag1/2 recombinase, but the precise position of the RSS with respect to the dyad axis governs the extent of inhibition.…”
Section: Significancementioning
confidence: 93%
“…BRM and BRG1 play important roles in the immune system SWI/SNF plays an important role in immune responses, T-cell development and recombination events (Golding et al, 1999;Agalioti et al, 2000;Kwon et al, 2000;Spicuglia et al, 2002;Morshead et al, 2003). The SWI/ SNF complexes have been shown to remodel chromatin in such a way as to drive consecutive developmental transitions in T cells in response to external stimuli.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…Variable-diversity-joining (V(D)J) recombination has also been shown to be mediated by SWI/SNF. BRG1 stimulates in vitro recombination of chromatin and is also bound to regions in the T-cell receptor (TCR) and immunoglobulin loci that take part in recombination events (Golding et al, 1999;Kwon et al, 2000;Spicuglia et al, 2002;Morshead et al, 2003;Patenge et al, 2004). More recent studies have shown SWI/SNF to be fundamental to the promoter-directed assembly of TCR-b (TCRB) genes (Osipovich et al, 2007); SWI/ SNF is recruited to promoters and then facilitates recombination by exposing segments of genomic DNA to V(D)J recombinase.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%